The Development of Wordwall-Based Digital Media for Teaching English Vocabulary for Sixth Graders - Dewi, Ni Putu Anjar Astriani; Utami, I.G.A Lokita Purnamika; Suprianti, G.A.P (Innovative: Journal Of Social Science Research, 2024)
This research aims todevelop Wordwall-based digital media for Englishsubjects focusing on teaching vocabulary to support the material in the Merdeka Curriculum textbook "My NextWords". The research design used in this research ist he D&D method using the ADDIE model by Richey & Klein (2014). This model consists of five stages, including: analysis, design, development, implementation and evaluation. There are five instruments used in this research, namely observation sheet, interview guidelines, module analysis matrix, media blueprint, and expert avaluation sheets. The subjects o fthis research were 5 students in grade 6 in the 2nd semester. The results of the data validation showed that the media developed was in the very good category with an average score of 94%. Thus, it can be concluded that Wordwall-based digital media is suitable for use as learning media for teaching. English vocabulary.